102 Clinical outcome in patients treated with Nobori, a new generation drug eluting stents in a real life setting. (22nd September 2015) - Fath-Ordoubadi, F; West, N; Talwar, S; Witherow, F; Hildick-Smith, D; Spyrou, N; Lim, P; Gorog, D; Fraser, D; El-Omar, M; danzi, G B
Abstract : Purpose: The use of drug eluting stents (DES) in every day clinical practice is not restricted to approved indications. The safety of this approach is not fully established. Therefore we initiated a large study to assess, in a real life setting, the usage practice and outcomes of patients treated with Nobori®, a new generation DES, coated only abluminally with a matrix of biodegradable polymer and Biolimus A9. Methods: As a part of the large NOBORI 2 study, one thousand consecutive patients treated with Nobori DES are enrolled in 125 centres across Europe and Asia. Patients were stratified in two pre-specified groups according to the risk factors and lesion characteristics. On-label, group 1 comprised patients with characteristics similar to pre-approval clinical trials; Off-label, group 2 was composed of patients with a higher complexity, which would be excluded from those trials. Primary endpoint was Target Lesion Failure (TLF), a composite of cardiac death, MI and target lesion revascularization (TLR) at 6 and 12 months, while secondary endpoints included Target Vessel Failure (TVF), stent thrombosis, death/MI, TLR, at 1, 6 and 12 months, 2, 3, 4 and 5 years. Data are entered in an electronic database and extensive on site and 100% on line monitoring for all patients are performed. Clinical events are adjudicated by an independent clinical event committee and all baseline angiograms are analysed by independent corelab. Results: In this, real-world population, 68% of patients (n=680) were treated for off-label indications. The most frequent off label use was acute myocardial infarction (37%), bifurcation stenting (26%), restenosis (8.4%), CTO (4.2%) and SVG (3.5%). Patients with off label indications had significantly more lesions treated (1.6 vs 1.1; p<0.01), more lesions in vessels smaller than 2.5 mm (39% vs 30%; p<0.01), and lesions >20 mm (52% vs 33% p<0.01) and more stents implanted (2.0 vs 1.2 p<0.01). There were no differences in cardiac risk factors. At 1-year follow-up, primary endpoint of TLF was 2.8% in on- and 4.4% in off-label treated patients, while TVF rate was 3.1% vs 5.4%. Stent thrombosis rate was similar in both groups (0.5% and 0.9%) and they were early. Abstract 102 Table 1 shows the individual component of MACE. Conclusion: Preliminary results of this large multicentre registry confirm excellent safety and efficacy profile of the Nobori stent in both groups of patients. Long term follow-up data for a large patient population as in this study, will better determine safety of current practice with this particular device.